PENGEMBANGAN BAHAN AJAR BERBASIS LITERASI BERCIRIKAN QUANTUM TEACHING UNTUK MENGOPTIMALKAN PEMBELAJARAN EFEKTIF DAN PRODUKTIF - Dwi Wahyuning Aisyah; Muhana Gipayana; Ery Tri Djatmika (Graduate School of Universitas Negeri Malang, 2017)
This study aims to produce teaching materials that support the implementation of School Literacy Movement Programme to improve the effectiveness and productivity of thematic learning in fourth grade of elementary school students. The product of the developed teaching materials is designed with the literacy as the substance and the framework of TANDUR on Quantum Teaching as its presentation systematics. The research and development method used by Dick & Carey model. The results of the development stage were found: (a) the less effective and productive causes of the fourth-grade students' learning, and (b) the need for literacy-based teaching materials and are characterized by relevant Quantum Teaching. At the development stage generated literature-based thematic students book is characterized by Quantum Teaching and teacher's manual that has been tested feasibility.Penelitian ini bertujuan mengahsilkan bahan ajar yang mendukung Gerakan Literasi Sekolah (GLS) untuk meningkatkan efektifitas dan produktivitas pembelajaran tematik kelas IV SD. Produk bahan ajar yang dikembangkan dirancang dengan literasi sebagai substansi dan kerangka perancangan TANDUR pada Quantum Teaching sebagai sistematika penyajiannya. Metode penelitian dan pengembangan yang digunakan adal model Dick & Carey. Hasilnya pada tahap pengembangan ditemukan: (a) penyebab kurang efektif dan produktifnya pembelajaran tematik siswa kelas IV, dan (b) kebutuhan bahan ajar berbasis literasi dan bercirikan Quantum Teaching yang relevan. Pada tahap pengembangan dihasilkan buku siswa dan buku panduan guru tematik berbasis literasi bercirikan Quantum Teaching teruji kelayakannya.